Developing A Web-Based Point-of-Sale Application using RAD: A Cafe Sonia Case Study - Jonathan Arya Wibowo; Muharman Lubis; Rio Guntur Utomo; Kobthong Ladkoom; Rahmat Yasirandi (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2026)
This study reports the development of a web-based Point of Sale (POS) system for Café Sonia, an MSME café setting where day-to-day transaction handling and reporting benefit from a workflow-aligned digital solution. The system was produced using Rapid Application Development (RAD) through short, stakeholder-driven iteration cycles with explicitly bounded scope and systematic feedback incorporation, resulting in an end-to-end POS flow from ordering to receipt and transaction history. Performance metrics reported in this paper are derived from a small-scale JMeter run and should be interpreted as an indicative baseline rather than evidence of peak-hour robustness. No dedicated usability evaluation was conducted; therefore, user-facing quality remains a pending empirical question that warrants task-based usability testing and standardized instruments such as the System Usability Scale (SUS) in subsequent iterations. Debates around RAD often hinge on a perceived tension between development speed and methodological accountability, particularly when systems must remain maintainable beyond the prototype stage. The Café Sonia case suggests that RAD can still yield a coherent, maintainable, and context-fit POS when iteration cycles are guided by stakeholders and the scope is clearly controlled. The novelty lies in providing case-based evidence of RAD’s practical effectiveness for delivering a customized MSME café POS, while the contribution is a traceable development pathway linking requirements capture, iterative prototyping artefacts, and scenario-based functional verification for reuse in comparable small-retail environments.